Neutrophils Release Metalloproteinases during Adhesion in the Presence of Insulin, but Cathepsin G in the Presence of Glucagon - Natalia V. Fedorova; Alexander L. Ksenofontov; Marina V. Serebryakova; Vladimir I. Stadnichuk; Tatjana V. Gaponova; Ludmila A. Baratova; Galina F. Sud’ina; Svetlana I. Galkina (Mediators of Inflammation)
In patients with reperfusion after ischemia and early development of diabetes, neutrophils can attach to blood vessel walls and release their aggressive bactericide agents, which damage the vascular walls. Insulin and 17β-estradiol (E2) relieve the vascular complications observed in metabolic disorders. In contrast, glucagon plays an essential role in the pathophysiology of diabetes. We studied the effect of hormones on neutrophil secretion during adhesion to fibronectin. Amino acid analysis revealed that proteins secreted by neutrophils are characterized by a stable amino acid profile enriched with glutamate, leucine, lysine, and arginine. The total amount of secreted proteins defined as the sum of detected amino acids was increased in the presence of insulin and reduced in the presence of glucagon. E2 did not affect the amount of protein secretion. Proteome analysis showed that in the presence of insulin and E2, neutrophils secreted metalloproteinases MMP-9 and MMP-8 playing a key role in modulation of the extracellular matrix. In contrast, glucagon induced the secretion of cathepsin G, a key bactericide protease of neutrophils. Cathepsin G can promote the development of vascular complications because of its proinflammatory activity and ability to stimulate neutrophil adhesion via the proteolysis of surface receptors.